The Effectiveness Of Nursery Rhymes In Teaching Vocabulary - Abdul Halim Muchlis (Tomorrow's Education Journal, 2024)
Based on the KTSP and K13 curriculum, the students were expected to master four skills in order to be able to use English communicatively. The students were expected to be able to understand and comprehend the meaning of the words. The aim of KTSP (Kurikulum Tingkat Satuan Pendidikan) and K13 (Kurikulum 2013) would not be successfully achieved if the language teaching did not consider the language components such as grammatical structure, vocabulary, spelling, pronunciation. Therefore, vocabulary needed to be mastered by the students since it was the basic thing in language The result of this research is expected to be useful theoretically and practically. Theoretically, it is expected to provide an empirical evidence to support the learning theory of vocabulary to improve the student’s vocabulary mastery, especially in using nursery rhymes. Practically, it is expected to be valuable information and give a meaningful contribution for teachers, students, and schools. Keywords: Nursery ryme, Vocabulary, Learning strategies